The effect of job satisfaction on turnover intentions in Star Hotel Semarang - Astadi Pangarso; M. Ario Julianto (Universitas Sebelas Maret, 2020)
This paper investigates the effect of job satisfaction on a turnover intention at the Star Hotel Semarang. We use 113 respondents using a non-probability sampling method at the Star Hotel Semarang. Using linear regression, we found the negative relationship between job satisfaction and turnover, suggesting a problematic association between job satisfaction and turnover intention. Therefore, our result suggests that other factors could be the obstacles to job satisfaction, such as the nature of the employee's work that was not under the job description, too strict supervision by the superiors, and a very long time to obtain the job promotion.